2021
DOI: 10.1155/2021/3536234
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Deficits in Patients with Poststroke Dementia: A Multimodal MRI Study

Abstract: Although many neuroimaging studies have reported structural and functional abnormalities in the brains of patients with cognitive impairments following stroke, little is known about the pattern of such brain reorganization in poststroke dementia (PSD). The present study was aimed at investigating alterations in spontaneous brain activity and gray matter volume (GMV) in PSD patients. We collected T1-weighted and resting-state functional magnetic resonance imaging data from 20 PSD patients, 24 poststroke nondeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Functional neuroimaging has made an essential contribution to revealing the neural mechanism after stroke. Resting-state functional magnetic resonance imaging (rs-fMRI) studies have indicated that the brain’s spontaneous neural activity and functional connectivity (FC) have changed in patients with cognitive impairment after stroke ( Peng et al, 2016 ; Cai et al, 2021 ). Peng et al (2016) found a significant decrease in regional homogeneity in the bilateral anterior cingulate cortex and left posterior cingulate cortex/precuneus in PSCI patients compared to healthy volunteers and post-stroke non-cognitive impairment patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional neuroimaging has made an essential contribution to revealing the neural mechanism after stroke. Resting-state functional magnetic resonance imaging (rs-fMRI) studies have indicated that the brain’s spontaneous neural activity and functional connectivity (FC) have changed in patients with cognitive impairment after stroke ( Peng et al, 2016 ; Cai et al, 2021 ). Peng et al (2016) found a significant decrease in regional homogeneity in the bilateral anterior cingulate cortex and left posterior cingulate cortex/precuneus in PSCI patients compared to healthy volunteers and post-stroke non-cognitive impairment patients.…”
Section: Introductionmentioning
confidence: 99%
“…Functional neuroimaging has made an essential contribution to revealing the neural mechanism after stroke. Resting-state functional magnetic resonance imaging (rs-fMRI) studies have indicated that the brain's spontaneous neural activity and functional connectivity (FC) have changed in patients with cognitive impairment after stroke (Peng et al, 2016;Cai et al, 2021). Peng et al (2016) found a significant decrease in regional homogeneity in the bilateral anterior cingulate cortex and left posterior cingulate cortex/precuneus in PSCI patients compared to healthy volunteers and post-stroke non-cognitive impairment Abbreviations: PSCI, post-stroke cognitive impairment; rs-fMRI, resting-state functional magnetic resonance imaging; FC, functional connectivity; dFNC, dynamic functional network connectivity; ICA, independent component analysis; HC, healthy control; hPSCI, hemorrhagic stroke with cognitive impairment; iPSCI, ischemic stroke with cognitive impairment; MoCA, Montreal Cognitive Assessment; IC, independent component; RSN, resting-state network; SD, standard deviation; CV, coefficient of variation; AUN, the auditory network; VN, the visual network; SMN, the sensorimotor network; PON, the occipital network; PreC, the precuneus network; DMN, the default mode networks; FPN, the frontoparietal network; ECN, the executive control network; SN, the salience network; CB, the cerebellar network.…”
Section: Introductionmentioning
confidence: 99%